Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 994 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Draba Dill. ex L.", "Geometry POLYGON((-120 -53,-120 13,-9 13,-9 -53,-120 -53))" ] } The dataset includes 994 records from 29 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000422-150204170955391/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences